High performance carbon free bifunctional air electrode for advanced zinc-air batteries. (1st April 2023) - Mainar, Aroa R.; Blázquez, J. Alberto; Frattini, Domenico; Enterría, Marina; Ortiz-Vitoriano, Nagore; Urdampilleta, Idoia; Grande, Hans-Jürgen
Abstract: Secondary zinc-air batteries (ZABs) offer a promising alternative for the future of sustainable energy storage. However, the current capability of secondary ZABs is far from satisfactory. The limitations for achieving high reversibility are mainly related to the bifunctional air electrodes as it severely hampers practical applications and commercialization of secondary ZABs. Many efforts have been devoted to the development of efficient and corrosion resistant bifunctional electrocatalysts towards oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). In ZABs, carbon is commonly used as conductive additive, however, it has been observed that carbon materials are not resistant to the high positive voltages applied in electrical recharge. In this work, the use of metallic nickel as alternative conductive additive in bifunctional air electrodes is explored and compared with carbon nanotubes (CNT). We demonstrate that the chemical resistance of CNT does not limit the electrode performance; but the density of the additive as well as its interaction with the active material is crucial for achieving long cycle life. The use of Ni as conductive agent in secondary ZABs boosted the cycle life by delivering more than 2, 400 cycles, in contrast to the 88 cycles delivered by the analogous carbon-based battery.